Numerical methods in geotechnical engineering [compact disc] : proceedings of the Sixth European Conference on Numerical Methods in Geotechnical Engineering, Graz, Austria, 6-8 September 2006 - European Conference on Numerical Methods in Geotechnical Engineering (6th : 2006 : Graz, Austria); Schweiger, Helmut F. (London : Taylor & Francis, 2006)
08